2022
DOI: 10.1097/mou.0000000000000976
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathologic characteristics to select patients for focal therapy or partial gland ablation of nonmetastatic prostate cancer

Abstract: Purpose of reviewFocal therapy or partial gland ablation for nonmetastatic prostate cancer is gaining popularity not just as an alternative to active surveillance, but as an acceptable alternative to whole gland therapy in appropriate cases. This review summarizes recent evidence to help select patients for optimal outcomes.Recent findingsRecommendations by expert panels have become less conservative with each meeting. As experience with older modalities for focal therapy grows, newer modalities continue to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In three cases, systematic biopsies did not yield any new diagnosis of csPCa but resulted in an up-grading of targeted biopsies from ISUP-GG 2 to ISUP-GG 3 in two cases, and to ISUP-GG 5 in one case. We consider these findings important for establishing the management of localized PCa with active surveillance or focal therapy ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In three cases, systematic biopsies did not yield any new diagnosis of csPCa but resulted in an up-grading of targeted biopsies from ISUP-GG 2 to ISUP-GG 3 in two cases, and to ISUP-GG 5 in one case. We consider these findings important for establishing the management of localized PCa with active surveillance or focal therapy ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of research has demonstrated that the majority, namely over 80%, of primary prostate cancers exhibit the presence of multiple distinct tumor foci [14]. The presence of multifocality holds the potential to exert a substantial impact on the strategic considerations for focal therapy in this particular patient cohort [15].…”
Section: Introductionmentioning
confidence: 99%
“…FT success largely revolves around appropriate patient selection and is paramount for optimal success. The ideal case for focal therapy should be an MRI visible significant lesion (PIRADS score ≥3), with a positive targeted biopsy for significant cancer (Gleason grade group 2–3), and insignificant or absent disease in the nontarget random biopsy areas ( 9 ). This could theoretically be applied to multiple areas of interest within the same gland if amenable.…”
Section: Introductionmentioning
confidence: 99%